Hubungan Kadar Timbal Dalam Darah Dengan Tekanan Darah Pada Tenaga Kerja Di Karoseri Semarang - Mutasir, Mutasir; Setiani, Onny; Sulistiyani, Sulistiyani (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Background: Lead is a toxic metal that can be contained in paint as a source of lead exposure in the air so significantly associated with blood lead levels (BLL). Statistically there is a significant association between BLL and blood pressure (BP). Preliminary study found that 10 workers of Carroseri Semarang found that 8 people (80%) had BLL above the threshold value, 7 people (70%) had a systolic blood pressure (SBP) above the limit normal and 8 people (80%) had diastolic blood pressure (DBP) at the upper limit of normal.Objective: This study aimed to determine the association between BLL and BP workers of Carroseri Semarang.Methods: It was an observational study with cross sectional approach. The population of this research was workers of Carroseri Semarang with a sample size of 34 people. Data collected by examining the levels of lead in paint, inspection level of lead in the air, checking blood lead levels and blood pressure checks.Results: This study showed the average level of lead in the paint measured was 59.39 ppm, level of lead in the air 0.002 ppm, BLL 28.97 mg/dL, SBP 122.76 mmHg and DBP 79.06 mmHg.Conclusion: All types of paint used in Carroseri Semarang contain lead under TLVs 600 ppm, the ambient workspace containing air lead levels below TLVs 0.05 ppm, the entire workforce part painting has undergone blood lead exposure >5Î¼g/dL, there is no association between BLL and SBP (p=0.465) and there a association between BLL and DBP (p =0.030).